2006
DOI: 10.1029/2005pa001187
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of geochemical and climatic signals in the Atlantic coral Montastraea faveolata

Abstract: [1] Monthly resolved, 41-year-long stable isotopic and elemental ratio time series were generated from two separate heads of Montastraea faveolata from Looe Key, Florida, to assess the fidelity of using geochemical variations in Montastraea, the dominant reef-building coral of the Atlantic, to reconstruct sea surface environmental conditions at this site. 18 O-sea surface temperature (SST) (R = À0.84) and Sr/Ca-SST (R = À0.86) calibration equations at Looe Key; however, these equations are different from previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
88
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(101 citation statements)
references
References 76 publications
8
88
5
Order By: Relevance
“…While brucite precipitation may fractionate oxygen and therefore influence the character of d 18 O available for calcification, it is reasonable to conclude that brucite formation has little or no influence on skeletal d 13 C because it lacks carbon. Smith et al (2006) found heterogeneity in Sr/Ca ratios across skeletal formations in M. faveolata, which, like d 13 C, cannot necessarily be explained by brucite precipitation, but instead likely occurs due to post-deposition thickening of the skeleton, underscoring the need to sample accurately along corallite walls. However, the clear existence of annual cycles in the records described here (e.g., Fig.…”
Section: Long-term Trendsmentioning
confidence: 93%
“…While brucite precipitation may fractionate oxygen and therefore influence the character of d 18 O available for calcification, it is reasonable to conclude that brucite formation has little or no influence on skeletal d 13 C because it lacks carbon. Smith et al (2006) found heterogeneity in Sr/Ca ratios across skeletal formations in M. faveolata, which, like d 13 C, cannot necessarily be explained by brucite precipitation, but instead likely occurs due to post-deposition thickening of the skeleton, underscoring the need to sample accurately along corallite walls. However, the clear existence of annual cycles in the records described here (e.g., Fig.…”
Section: Long-term Trendsmentioning
confidence: 93%
“…In addition, of those coral-based studies undertaken at annual to pent-annual resolutions (Dunbar et al 1994;Cole et al 2000;Hendy et al 2002;Pelejero et al 2005;Calvo et al 2007;Linsley et al 2008;Abram et al 2009;Wei et al 2009;Deng et al 2013;Zinke et al 2014), few have focused on the replication of the lowresolution geochemical records of multiple coral cores. Some studies have evaluated the climatic significance of annual coral records averaged using monthly or sub-annual values from each year (Lough 2004;Smith et al 2006;Pfeiffer et al 2009). However, such approaches may suffer from biases caused by the attenuation of the coral geochemical records, which leads to an overestimate of the changes in sea surface temperature (SST) over decadal to millennial timescales (Gagan et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, Smith et al, 2006] predict SST spanning more than 10C at a given Sr/Ca ratio, and make climatic interpretations using this species difficult. Evidence for growth-related effects on Sr/Ca in other coral genera [deVilliers et al, 1995;Goodkin et al, 2005] raises the possibility that disparate Montastrea calibrations may be related to growth.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…Nevertheless, interpreting coral geochemistry in terms of climatic parameters is not always straightforward [Lough, 2004]. For example, Sr/Ca-SST calibrations derived to date from single colonies of the Atlantic coral Montastrea, a predominant genus in both modem and fossil reefs [Weil and Knowlton, 1994;Hubbard et al, 2005] show significant, yet unexplained differences [Swart et al, 2002;Smith et al, 2006]. This implies that paleo-SST estimates derived using these calibrations depend heavily on which calibration is applied.…”
Section: Introductionmentioning
confidence: 99%